PENGUKURAN PERFORMANSI SUPPLIER DENGAN MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS (DEA) DI PT MISAJA MITRA PATI JAWA TENGAH - Suryani, Lilis; Setyaningsih, Ira (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
This research discusses the measurement of the relative efficiency of the supplier’s performance using Data Envelopment Analysis (DEA) . The supplier’s perfor-mance variable is modificated from research . Input variable is the total purchase price. The out-put variables are the ability to fulfill the order quantity, the quality of shrimp, delivery performance, and supplier’s track record. There are 10 suppliers used in this research. 4 suppliers have good performance (efficiency score = 1) are B, C, D, and F. The best supplier is D who has 1.21 super efficiency’s score.